A Closed Metallomolecular Cage that can Open its Aperture by Disulfide Exchange. Issue 6 (15th January 2019) - Akine, Shigehisa; Miyashita, Masato; Nabeshima, Tatsuya
Abstract: Invited for the cover of this issue is the group of Shigehisa Akine at Kanazawa University and Tatsuya Nabeshima at the University of Tsukuba. The image, designed by Prof. Akine, depicts a visualization of the possible "open" intermediate molecule that allows a guest to enter and exit. Read the full text of the article at10.1002/chem.201805359 . Abstract : " The challenge was to introduce a dynamic open/close function in a metal‐containing cage without affecting the coordination structure ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 1432 ff. (DOI:10.1002/chem.201805359 ).